Bilateral Synchronous Granulomatous Orchitis in a Patient with Erectile Disfunction: Clinical and Pathologic Study of the Case - M. Rodriguez Peña; D. Moreno (Case Reports in Urology)
A 50-year-old male patient presented with erectile failure and loss of libido. In the physical examination, there were stone-hard indurations in his bilateral testes. The ultrasonographic study demonstrated multiple hypoechoic areas in the testes and normal epididymis. Since the lesion was presumed as malignancy, bilateral inguinal exploration was performed and intraoperative frozen biopsies were studied and diagnosed as inflammatory process. Nevertheless, we decided to perform left orchiectomy to a deeper histopathologic analysis which revealed granulomatous orchitis, mastocytosis, and severe depletion of Leydig cells at the testicular interstitium. Differential diagnosis between testicular tumor and granulomatous orchitis is very difficult in any examination except by histological findings. Bilateral cases of this pathology are relatively rare, but it is necessary to distinguish them from the testicular tumor before surgical intervention to avoid an unnecessary orchiectomy.